PENGARUH KEPATUHAN WAJIB PAJAK DAN PEMERIKSAAN PAJAK TERHADAP PENERIMAAN PPh PASAL 25/29 PADA KANTOR PELAYANAN PAJAK PRATAMA SEMARANG SELATAN (Students' Journal of Accounting and Banking, 2013)
This study aims to determine and analyze the effect of taxpayer compliance and tax audit to income of Article 25/29 at KPP Pratama Semarang Selatan. This study uses quantitative data using secondary data obtained from the KPP Pratama Semarang Selatan. The sample used in this study i.e. from January 2009 to December 2011. Analysis of the data used in this study are using multiple linear regression analysis. The results of this study states that taxpayer compliance and the amount of the tax auditing influential significant positive effect to the receipt of Income Tax Article 25/29 in KPP Pratama Semarang Selatan.Keywords: the influence of taxpayer comliance and nuber of tax audit to income tax recept article 25/29 Kantor Pelayanan Pajak Pratama Semarang Selatan